A central role for R7bp in the regulation of itch sensation. Issue 5 (May 2017) - Pandey, Mritunjay; Zhang, Jian-Hua; Mishra, Santosh K.; Adikaram, Poorni R.; Harris, Benjamin; Kahler, John F.; Loshakov, Anna; Sholevar, Roxanne; Genis, Allison; Kittock, Claire; Kabat, Juraj; Ganesan, Sundar; et al.
Abstract : Abstract: Itch is a protective sensation producing a desire to scratch. Pathologic itch can be a chronic symptom of illnesses such as uremia, cholestatic liver disease, neuropathies and dermatitis, however current therapeutic options are limited. Many types of cell surface receptors, including those present on cells in the skin, on sensory neurons and on neurons in the spinal cord, have been implicated in itch signaling. The role of G protein signaling in the regulation of pruriception is poorly understood. We identify here 2 G protein signaling components whose mutation impairs itch sensation. R7bp (a.k.a. Rgs7bp) is a palmitoylated membrane anchoring protein expressed in neurons that facilitates Gαi/o -directed GTPase activating protein activity mediated by the Gβ5/R7-RGS complex. Knockout of R7bp diminishes scratching responses to multiple cutaneously applied and intrathecally-administered pruritogens in mice. Knock-in to mice of a GTPase activating protein-insensitive mutant of Gαo ( Gnao1 G184S/+) produces a similar pruriceptive phenotype. The pruriceptive defect in R7bp knockout mice was rescued in double knockout mice also lacking Oprk1, encoding the G protein-coupled kappa-opioid receptor whose activation is known to inhibit itch sensation. In a model of atopic dermatitis (eczema), R7bp knockout mice showed diminished scratching behavior and enhanced sensitivity to kappa opioid agonists. Taken together, our results indicate that R7bp is a key regulator of itch sensation and suggest the potential targeting of R7bp-dependent GTPase activating protein activity as a novel therapeutic strategy for pathological itch. Abstract : Knockout of R7bp significantly impairs acute and chronic itch sensation, suggesting inhibition of R7bp function could represent a novel therapeutic strategy for pathological itch.